Effectiveness of Using Chicken Eggshells as a Biocoagulant in Groundwater Treatment - Rifqyawarman, Hanief; Riana Ayu Kusumadewi; Aphirta, Sarah; Winarni, Winarni (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
The groundwater in Kota Bambu Selatan, West Jakarta, has high levels of turbidity and TDS. Therefore, it is necessary to be treated in order to comply with the regulations outlined in the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning Environmental Health standards. This study aims to investigate the effectiveness chicken eggshells as a biocoagulant for treating this groundwater. The techniques employed encompassed coagulation and flocculation, involving different coagulation G.td values (17,000, 34,000, 48,000, and 96,000) and a range of biocoagulant doses (100-500 mg/L). The outcomes of the treatment revealed that the utilization of chicken eggshells as a biocoagulant led to the removal of 47.14% of TDS and 97.17% of turbidity. The cost associated with implementing chicken eggshells as a biocoagulant amounted to IDR 230.70 per liter. In light of these findings, it can be deduced that chicken eggshells serve as an effective biocoagulant for reducing TDS and turbidity in the groundwater treatment.